2014
DOI: 10.1016/j.childyouth.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

“In the name of the children”: Public policies for children in out-of-home care in Chile. Historical review, present situation and future challenges

Abstract: Take down policyIf you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim. Download date: 05. May. 2021 1 "In the name of the Children": Public Policies for Children in out-of-home care in Chile. Historical review, present situation and future challenges (Children and Youth Services Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 20 publications
(16 reference statements)
1
18
0
6
Order By: Relevance
“…The vast majority of participants did not have any specialized professional training in education or childcare. Characteristics of this sample of residential homes are representative of the general characteristics in the regions of the country included in the study regarding, number of children, caregiver ratios, staff turnover, and level of training, with the only exclusion (due to voluntary participation) of a few bigger and older institutions that still exist in the country (Garcia Quiroga & Hamilton-Giachritsis, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of participants did not have any specialized professional training in education or childcare. Characteristics of this sample of residential homes are representative of the general characteristics in the regions of the country included in the study regarding, number of children, caregiver ratios, staff turnover, and level of training, with the only exclusion (due to voluntary participation) of a few bigger and older institutions that still exist in the country (Garcia Quiroga & Hamilton-Giachritsis, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…In Chile, an important debate has taken place concerning the quality of care for children in need. Foster care has been implemented, with numerous difficulties, and new quality standards for institutional setting have been established (Garcia Quiroga & Hamilton-Giachritsis, 2014). A recent study reported a positive impact of a pilot intervention program with caregivers working in an infant home (Lecannelier et al, 2014).…”
mentioning
confidence: 99%
“…Similarly, length of placement can have a positive effect if mediated by quality of care. The aim, then, should be to provide stability in high quality placements, rather than using a series of short placements with multiple changes and the inherent negative impact on attachment formation (Garcia Quiroga and Hamilton-Giachritsis 2014 ). Some characteristics of caregivers that go beyond the usual assessments have been shown to impact on attachment security.…”
Section: Conclusion and Implications For Practicementioning
confidence: 99%
“…Children and adolescents in out-of-home care can generally be placed there either by child welfare (civil law) or juvenile justice (criminal law) authorities. The quality of structures and processes in different care settings within and across child welfare and juvenile justice systems varies substantially between countries with different socioeconomic opportunities and policies [8][9][10][11]. In general, adolescent offenders are marked by highly elevated rates of trauma, psychopathology, and other psychosocial problems [12,13], while adolescents in child welfare placements often show delinquent behavior in addition to similarly elevated rates of psychosocial treatment needs [3,14].…”
Section: Introductionmentioning
confidence: 99%